To Serve and to Lead : A History of the Diocesan Boys' School in Hong Kong - Fung, Y. W. (Book collections on Project MUSE., 2009)
The history of the Diocesan Boys' School (DBS)--in 1869--dates back to the very early days of Hong Kong. DBS's development has since been closely linked with that of Hong Kong.